Editorial for 'New talent' collection: introducing New Talent in chemistry and material science. Issue 8 (15th August 2018) - Sanders, Jeremy K. M.; Stace, Anthony
Abstract : We introduce 14 articles published as part of the 'New talent' special collection of invited articles to showcase some of the exciting work being funded by the Royal Society. As Royal Society University Research Fellows or Dorothy Hodgkin Fellowship holders, the contributors to this collection are rising stars in their areas of research. This collection also illustrates the close collaboration between Royal Society Open Science and the Royal Society of Chemistry. The collection spans the range of the chemical and material sciences, reflecting the breadth of research areas receiving Royal Society grant support.